The relationship between Chinese medical students' learning motivation and learning engagement: a network analysis - Wang, Dengqin; Song, Peibo; Zhang, Qianqian; Zhao, Huili; Zhuang, Bo (Frontiers in Psychology, 2025)
ObjectiveThis study aims to elucidate the internal relationships among the dimensions of learning motivation and learning engagement in Chinese medical students by examining the network structure of these constructs and exploring potential differences under different training models.MethodsA network analysis approach was adopted to analyze survey data from 499 Chinese medical students. A comprehensive network encompassing dimensions of learning motivation and learning engagement was constructed, followed by two sub-networks respectively focusing on tuition-exempt (government-funded) medical students and self-funded medical students. Comparisons were then made to highlight structural differences across these sub-networks.ResultsIn the overall network, “challenge” had the highest expected influence index, followed by “focusing on interpersonal competition.” These two dimensions formed the central hub of the network and exerted significant influence on the network's overall structure. Comparative analyses showed that in the government-funded student network, “focusing on interpersonal competition” exhibited the highest expected influence, whereas “challenge” was most influential in the self-funded student network.ConclusionThis study offers a novel perspective for understanding medical students' learning motivation and behavioral patterns, thereby expanding research avenues in the field of medical education. The findings suggest that targeted interventions on these core dimensions can effectively enhance learning engagement among medical students.